Empirical determinants of relationship lending - Elsas, Ralf (Journal of Financial Intermediation, 2005)
This paper analyzes determinants of the incidence of relationship lending. We explore self-assessments of German universal banks with respect to their Hausbank status in corporate lending and relate loan contract and borrower characteristics to this attribution. The analysis shows that Hausbank status is positively related to better access to information and the bank's influence on borrower management. While the duration of the bank–borrower relationship is not related to Hausbank status, banks are more likely to be Hausbanks when their share of borrower debt financing is higher and when the number of bank relationships is lower. We also find that the likelihood of observing a Hausbank relationship is non-monotonically related to bank concentration in local debt markets. For low and intermediate values of concentration, Hausbank relationships become more likely as competition increases. This contradicts the conjecture that relation lending requires monopolistic market structures. Nevertheless, in highly concentrated markets, less competition fosters Hausbank relationships.